PISA XALQARO BAHOLASH TADQIQOTIDA TABIIY-ILMIY SAVODXONLIKNING BAHOLANISHI - Isakova, M (Журнал математики и информатики, 2024)
This article offers suggestions on the assessment and importance of science literacy in the PISA International Assessment Program. Informational on the professional activity of specialists teaching natural sciences and the current state of demand is included. Measures to improve natural-scientific literacy in the PISA International Assessment Program are discussed.